Secure Quantum Encryption - St-Jules, Michael (Université d'Ottawa / University of Ottawa, 2016)
To the field of cryptography, quantum mechanics is a game changer. The exploitation of quantum mechanical properties through the manipulation of quantum information, the information encoded in the state of quantum systems, would allow many protocols in use today to be broken as well as lead to the expansion of cryptography to new protocols. In this thesis, quantum encryption, i.e. encryption schemes for quantum data, is defined, along with several definitions of security, broadly divisible into semantic security and ciphertext indistinguishability, which are proven equivalent, in analogy to the foundational result by Goldwasser and Micali. Private- and public-key quantum encryption schemes are also constructed from quantum-secure cryptographic primitives, and their security is proven. Most of the results are in the joint paper Computational Security of Quantum Encryption, to appear in the 9th International Conference on Information Theoretic Security (ICITS2016).
Keywords: quantum cryptography; quantum encryption; semantic security; indistinguishability; indistinguishable encryptions; CPA; CCA; CCA1; pseudorandom generator; pseudorandom function; one-way function; trapdoor one-way permutation; chosen plaintext attack; chosen ciphertext attack